2012
DOI: 10.1088/2041-8205/763/1/l6
|View full text |Cite
|
Sign up to set email alerts
|

TESTING DIAGNOSTICS OF NUCLEAR ACTIVITY AND STAR FORMATION IN GALAXIES AT z > 1

Abstract: We present some of the first science data with the new Keck/MOSFIRE instrument to test the effectiveness of different AGN/SF diagnostics at z ∼ 1.5. MOSFIRE spectra were obtained in three H-band multi-slit masks in the GOODS-S field, resulting in two hour exposures of 36 emission-line galaxies. We compare X-ray data with the traditional emission-line ratio diagnostics and the alternative mass-excitation and color-excitation diagrams, combining new MOSFIRE infrared data with previous HST/WFC3 infrared spectra (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 52 publications
(71 reference statements)
5
65
0
Order By: Relevance
“…Barro et al (2014) find in the GOODS-S field that compact starforming sources at z ∼ 2 are more likely to host X-ray bright AGN compared to more extended counterparts. Trump et al (2013) also show that clumpy and compact galaxies at z ∼ 0.11 harbor a high fraction of AGN in the SDSS survey. Kocevski et al (2017) confirm that ∼ 40% of M > 10 10 M compact SF galaxies observed in four fields of candels with 3 > z > 1.4 host an AGN.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Barro et al (2014) find in the GOODS-S field that compact starforming sources at z ∼ 2 are more likely to host X-ray bright AGN compared to more extended counterparts. Trump et al (2013) also show that clumpy and compact galaxies at z ∼ 0.11 harbor a high fraction of AGN in the SDSS survey. Kocevski et al (2017) confirm that ∼ 40% of M > 10 10 M compact SF galaxies observed in four fields of candels with 3 > z > 1.4 host an AGN.…”
Section: Introductionmentioning
confidence: 54%
“…More compact and star-forming galaxies have a higher probability of hosting a more luminous AGN (up to Lx ∼ 10 44 erg/s) in the simulation. The simulation is able to reproduce the qualitative trends found in several observational studies for AGN fractions in different galaxy types (Trump et al 2013;Barro et al 2014;Kocevski et al 2017).…”
Section: Correlation Between Galaxy Structural Properties and Bh Actimentioning
confidence: 64%
“…A link between clumpy disks and AGN activity atz 0.7 has been reported by Bournaud et al (2012), yet for luminosities well below our cutoff, i.e., < L 10 X 42 erg s −1 , arguing that this mechanism would only account for very modest levels of activity at these redshifts. Atz 2, however, Trump et al (2014) found similar levels of AGN activity in clumpy and smooth disks, ruling out violent disk instabilities as a dominant or more efficient BH fueling mechanism.…”
Section: Most Active Disk Galaxies Are Unbarredmentioning
confidence: 85%
“…The galaxies in SIGMA are located in the UDS, GOODS-S, and GOODS-N fields. Spectra were taken with the MOSFIRE spectrograph (McLean et al 2010(McLean et al , 2012 on the Keck I telescope as a part of the TKRS-2 survey (Wirth et al 2015) and were also published in Trump et al (2013) and Barro et al (2014). The slits were 0 7 wide and the spectral resolution wasR…”
Section: Sigma Samplementioning
confidence: 99%